Marasas et al. 1984 "Toxigenic Fusarium Species: Identity and Mycotoxicology" revisited. (2nd November 2018) - O'Donnell, Kerry; McCormick, Susan P.; Busman, Mark; Proctor, Robert H.; Ward, Todd J.; Doehring, Gail; Geiser, David M.; Alberts, Johanna F.; Rheeder, John P.
ABSTRACT: This study was conducted to determine the species identity and mycotoxin potential of 158 Fusarium strains originally archived in the South African Medical Research Council's Mycotoxigenic Fungal Collection (MRC) that were reported to comprise 17 morphologically distinct species in the classic 1984 compilation by Marasas et al., Toxigenic Fusarium Species: Identity and Mycotoxicology . Maximum likelihood and maximum parsimony molecular phylogenetic analyses of single and multilocus DNA sequence data indicated that the strains represented 46 genealogically exclusive phylogenetically distinct species distributed among eight species complexes. Moreover, the phylogenetic data revealed that 80/158 strains were received under a name that is not accepted today (ex F. moniliforme ) or classified under a different species name. In addition, gas chromatography–mass spectrometry (GC-MS) and/or high-performance liquid chromatography–mass spectrometry (HPLC-MS)-based mycotoxin analyses were conducted to determine which toxins the strains could produce in liquid and/or solid cultures. All of the trichothecene toxin–producing fusaria were nested within the F. sambucinum (FSAMSC) or F. incarnatum-equiseti (FIESC) species complexes. Consistent with this finding, GC-MS analyses detected trichothecenes in agmatine-containing broth or rice culture extracts of all 13 FSAMSC and 10/12 FIESC species tested. Species in six and seven of the eight species complexes were able to produce moniliformin and beauvericin, respectively, whereas B-type fumonisins were only detected in extracts of cracked maize kernel cultures of three species in the F. fujikuroi (FFSC) species complex.